THE IMPROVEMENT JAVANESE ALPHABETH WRITING SKILL WITH STRATEGIES MAKE A MATCH FOR CLASS VIII B STUDENTS SMP NEGERI 3 SATU ATAP KALIANGKRIK ACADEMIC YEAR 2021/2022 - Hasan, Nasrul; Santosa, Eko; Rochimansyah, Rochimansyah (Jurnal Ilmu Bahasa, Sastra dan Pengajarannya, 2024)
This study aims to describe the learning steps using make a match learning strategy to improve Javanese script writing skills in class VIII B students of SMP Negeri 3 Satu Atap Kaliangkrik Magelang and to improve Javanese script writing skills in class VIII B students of SMP Negeri 3 Satu Atap Kaliangkrik by using make a match strategy. This study used a class action research design which was carried out in two cycles, namely cycle I and cycle II. The object of this research was the students of class VIII B SMPN 3 Satu Atap Kaliangkrik Magelang totaling 34 students. Data collection used test and non-test techniques. Qualitative descriptive technique was used to analyze the data of Javanese script writing skills using make a match learning method. The results showed that the steps in learning using two cycles, namely cycle I and cycle II. In cycle I and cycle II using the make a match method to improve the ability to write Javanese characters. Students' activeness in learning to write Javanese characters using the make a match method shows an increase in students' motivation and interest in writing using Javanese characters. Students become more active and willing to ask questions related to material that has not been understood. The ability to write Javanese script for students in class VIII B in the 2021/2022 school year using the make a match method has increased significantly. Based on the results of the study, there was an increase in the average ability to write Javanese characters from cycle I of 65.49 and increased to 81.25.